STRATEGI GURU PAI DALAM MELAKSANAKAN PEMBELAJARAN BERBASIS PENELITIAN TINDAKAN KELAS PADA SDN PERCONTOHAN TOLITOLI - Ni’mah Wahyuni (Pusat Riset dan Inovasi Nasional, 2021)
This study discusses the PAI Teacher's Strategy in carrying out Classroom Action Research-based learning. This study aims (1) to find out how the PAI teacher's strategy is in carrying out Classroom Action Research-based learning at Tolitoli Pilot Elementary School, (2) to find out the inhibiting and supporting factors for implementing Classroom Action Research at Tolitoli Pilot Elementary School. The main problems studied in this research are; what is the PAI teacher's strategy in carrying out Classroom Action Research-based learning at Tolitoli Pilot Elementary School, the supporting and inhibiting factors for implementing Classroom Action Research at Tolitoli Pilot Elementary School. This research is a qualitative descriptive research using the approach; pedagogical. The data sources in this study were: (1) school principals (2) Islamic Religious Education teachers and TU as complementary data. Data was collected using techniques, interviews, observation and documentation. The collected data is then processed and analyzed in three ways: data reduction, data display, verification or conclusion. As the implications of research. PAI teachers can always conduct Classroom Action Research in order to improve the quality of learning both in class, themselves and others and can improve their professionalism as a teacher. finding solutions to solving teacher learning in the classroom.